2021
DOI: 10.1111/dme.14669
|View full text |Cite
|
Sign up to set email alerts
|

Consensus report: Definition and interpretation of remission in type 2 diabetes

Abstract: A consensus report of a particular topic contains a comprehensive examination and is authored by an expert panel (i.e., consensus panel) and represents the panel's collective analysis, evaluation, and opinion. The need for a consensus report arises when clinicians, scientists, regulators, and/or policy makers desire guidance and/or clarity on a medical or scientific issue related to diabetes for which the evidence is contradictory, emerging, or incomplete. Consensus reports may also highlight gaps in evidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(76 citation statements)
references
References 38 publications
1
69
0
6
Order By: Relevance
“…Our analysis regarding remission of type 2 diabetes has several limitations. First, according to the American Diabetes Association (ADA), type 2 diabetes remission should be considered after maintaining normal blood sugar levels for 3 months or more (68). However, we can notice that the definition varies among the studies, as reported in Supporting Information Table S15.…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis regarding remission of type 2 diabetes has several limitations. First, according to the American Diabetes Association (ADA), type 2 diabetes remission should be considered after maintaining normal blood sugar levels for 3 months or more (68). However, we can notice that the definition varies among the studies, as reported in Supporting Information Table S15.…”
Section: Discussionmentioning
confidence: 99%
“…In the initial consensus from 2009, partial remission and complete remission were diagnosed for prediabetes and normal blood glucose levels, respectively, and criteria subdivided into prolonged remission were presented when complete remission status was more than 5 years [ 13 ]. However, in the new consensus from 2021, remission was changed to a single diagnostic standard, and the classification of the period was removed considering the complexity and lack of evidence for the standards of blood glucose level and maintenance period [ 14 ].…”
Section: Can Diabetes Be Cured? Definition Of Remissionmentioning
confidence: 99%
“… Adapted from Buse et al [ 13 ], and Riddle et al [ 14 ], with permission from Oxford University Press. …”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, in this issue, we publish the consensus definition of diabetes remission and look forward to publishing literature contributing to the basic and clinical science evidence base to better understand remission. 9 It is important to note that all care processes must be continued for people in remission, with potential impact on the cost-effectiveness of interventions supporting remission, and it is unclear whether, and by how much, remission impacts cardiovascular risk. These important questions can now be addressed using an agreed definition to ensure homogeneous reporting.…”
Section: Taking Back Controlmentioning
confidence: 99%